Targeting of lanthanide(III) chelates of DOTA-type glycoconjugates to the hepatic asyaloglycoprotein receptor: cell internalization and animal imaging studies - Prata, M. I. M. (2006)
The characterization of a new class of hydrophilic liver-targeted agents for gamma-scintigraphy and MRI, consisting, respectively, of [153Sm]3+ or Gd3+ complexes of DOTA monoamide or bisamide linked glycoconjugates (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), is reported. In vitro studies show high uptake of radiolabeled [153Sm]-DOTAGal2 by the human hepatocyte carcinoma cell line Hep G2 containing the asialoglycoprotein receptor (ASGP-R), which is decreased to less than 50% by the presence of its high-affinity ligand asialofetuin (ASF). In vivo biodistribution, gamma-imaging and pharmacokinetic studies on Wistar rats using the [153Sm]3+-labeled glycoconjugates show a high uptake in the receptor-rich organ liver of the radiolabeled compounds containing terminal galactosyl groups, but very little uptake for those compounds with terminal glycosyl groups. Blocking the receptor in vivo reduced liver uptake by 90%, strongly suggesting that the liver uptake of these compounds is mediated by their binding to the asyaloglycoprotein receptor (ASGP-R). This study also demonstrated that the valency increase improves the targeting capability of the glycoconjugates, which is also affected by their topology. However despite the specific liver uptake of the radiolabeled galactose-bearing multivalent compounds, the animal MRI assessment of the corresponding Gd3+ chelates shows liver-to-kidney contrast effects which are not significantly better than those shown by GdDTPA. This probably results from the quick wash-out from the liver of these highly hydrophilic complexes, before they can be sufficiently concentrated within the hepatocytes via receptor-mediated endocytosis. Copyright © 2006 John Wiley & Sons, Ltd.